MODERN PEDAGOGICAL TECHNOLOGIES FOR CULTIVATING PATRIOTIC SPIRIT AMONG STUDENTS TOWARD HISTORICAL FIGURES ON THE BASIS OF OUR ANCESTRAL HERITAGE (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article examines how modern pedagogical technologies can be employed to cultivate a stable patriotic spirit among students through value-oriented engagement with historical figures, interpreted as part of ancestral heritage. The study positions patriotic education not as declarative loyalty, but as a developmental process that integrates historical consciousness, moral judgment, civic responsibility, and personal meaning-making. In teacher education, this process is especially critical because future educators transmit civic values through curriculum choices, classroom discourse, and the learning environment they design. The paper conceptualizes ancestral heritage as an educational resource comprising biographies of exemplary historical figures, cultural memory, ethical narratives, and locally meaningful traditions that can be translated into learning tasks without turning instruction into memorization or ideological slogans. A pedagogical framework is proposed that blends inquiry-based learning, project work, dialogic instruction, reflective writing, and community-linked activities to build students’ emotional connection and rational understanding. The framework also incorporates media and source criticism, enabling learners to distinguish reliable historical evidence from simplified myths and to develop respect toward multiple perspectives while maintaining a coherent civic position. Methodologically, the study outlines a design-based approach for integrating these technologies into teacher-training courses and school practicum, including lesson scenarios, assessment indicators, and reflection tools. Expected outcomes include strengthened historical empathy, increased civic motivation, improved ability to articulate values using evidence, and enhanced readiness to implement patriotic education ethically and inclusively in diverse classrooms. The article argues that the most effective modern technologies are those that create structured opportunities for students to encounter historical figures as moral and civic reference points, to compare past and present responsibilities, and to translate admiration into constructive social behavior rather than symbolic rhetoric.